Cross‐cultural care encounters in paediatric care: minority ethnic parents' experiences. Issue 1 (22nd January 2016) - Tavallali, Azar Gashasb; Jirwe, Maria; Kabir, Zarina Nahar
Abstract : Background: Because of worldwide migration, the healthcare staff in general as well as in paedi"atric care specifically is challenged increasingly by people from various ethnic backgrounds. The challenge is related to providing culturally competent care and effectively communicating with people from diverse cultural and ethnic backgrounds who have different health beliefs, practices, values and languages. This also applies to the Swedish society and to Swedish paediatric care. Aim: The purpose of this study was to describe the expectations and experiences of cross‐cultural care encounters among minority ethnic parents in Swedish paediatric care. Method: A qualitative design was used in the study. Data were collected using semi‐structured interviews between October 2011 and March 2012. The sample consisted of 12 parents of minority ethnic backgrounds who had their child in a ward at a children's hospital in the Stockholm County Council. The interviews were analysed using manifest content analysis. Ethical considerations: The Regional Ethical Review Committee approved the study (Ref: Nr: 2011/927‐31/5). Results: The analysis of the interviews led to three categories: fundamentals in nursing, cultural sensitivity and understanding, and influencing conditions. Conclusions: Generic knowledge and skills of nurses outweighed the need for the nurses to have culture‐specific knowledge of their patients or relatives in cross‐cultural care encounters. Language skills and the availability of bilingual nurses in a multi‐ethnic society can facilitate communication and increase parents' satisfaction in cross‐cultural care encounters.